Goal-directed-perfusion in neonatal aortic arch surgery - Cesnjevar, Robert; Purbojo, Ariawan; Münch, Frank; Juengert, Joerg; Rueffer, Andre (Translational Pediatrics, 2016)
Reduction of mortality and morbidity in congenital cardiac surgery has always been and remains a major target for the complete team involved. As operative techniques are more and more standardized and refined, surgical risk and associated complication rates have constantly been reduced to an acceptable level but are both still present. Aortic arch surgery in neonates seems to be of particular interest, because perfusion techniques differ widely among institutions and an ideal form of a so called "total body perfusion (TBP)" is somewhat difficult to achieve. Thus concepts of deep hypothermic circulatory arrest (DHCA), regional cerebral perfusion (RCP/with cardioplegic cardiac arrest or on the perfused beating heart) and TBP exist in parallel and all carry an individual risk for organ damage related to perfusion management, chosen core temperature and time on bypass. Patient safety relies more and more on adequate end organ perfusion on cardiopulmonary bypass, especially sensitive organs like the brain, heart, kidney, liver and the gut, whereby on adequate tissue protection, temperature management and oxygen delivery should be visualized and monitored.
EVALuna2:34094